The Role of Multi‐Stakeholder Collaboration and Community Consensus Building in Improving Identification and Early Diagnosis of Autism in Low‐Resource Settings. (August 2016) - Murillo, Lucia; Shih, Andy; Rosanoff, Michael; Daniels, Amy M.; Reagon, Kara
Abstract : Objective: Research has demonstrated that early intervention for children with autism can lead to improvements in core symptoms and enhance cognition, adaptive functioning, and quality of life. Unfortunately, most children are diagnosed too late to fully benefit from these services. Even in regions where diagnosis of autism can reliably be made, families often face additional barriers in accessing quality services. This article describes case examples in which Autism Speaks' Global Autism Public Health (GAPH) Initiative partnered with communities to facilitate a process of multi‐stakeholder collaboration to better understand local autism priorities related to awareness activities, early diagnosis, and developing autism surveillance systems. Method: This paper utilised a nested case study to demonstrate how GAPH employs multi‐stakeholder collaboration, community‐based participatory research (CBPR) and consensus building to enhance early identification in low‐resource settings. Each of these processes influenced different phases of the projects. Results: In the first example, Autism Speaks adopted a CBPR approach to understand and address barriers to help‐seeking behaviour among the Korean community affected by autism in New York City. The second example describes an international effort to develop open‐source screening and diagnostic tools for autism that can be delivered by non‐specialists in low‐resource settings. The last example describes efforts to facilitate the development of an autism registry in Ireland to inform health policy decisions. Conclusions: Collectively, these examples outline approaches the GAPH initiative uses to support global communities in working to overcome challenges related to the needs of individuals with autism and their families.